Oversimplifying Teaching of the Control of Variables Strategy - Lorch, Jr., Robert F. (Madrid : Colegio Oficial de Psicólogos de Madrid, 2020)
Two experiments compared closely related interventions to teach the control of variables strategy (CVS) to fourth-grade students. Over the two experiments, an intervention first developed by Chen and Klahr (1999) was most effective at helping students learn how to design and evaluate single-factor experiments. In Experiment 1, attempts to reduce the cognitive load imposed by Chen and Klahr's basic teaching intervention actually produced poorer learning and transfer of CVS. In Experiment 2, attempts to simplify Chen and Klahr's algorithm for teaching students how to set up a valid experimental design also produced poorer learning and transfer of CVS. Both experiments illustrate that oversimplifying a domain or the logic behind controlling variables can undermine the effectiveness of an intervention designed to teach CVS.
En inglés; resúmenes en español e inglés.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Descripción basada en Psicología educativa: revista de los psicólogos de la educación, vol. 26, n. 1 (enero 2020), P. 7-16.
Recurso electrónico. Santa Fe, Arg.: elibro, 2024. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Diseño instructivo; Educación científica.; Educación en ciencias elementales; Artículos electrónicos.